Faktor gaya hidup Faktor Gaya Hidup yang Mempengaruhi Kejadian Diabetes Mellitus Di Kota Padang Tahun 2020 - Dafriani, Putri; Sari, Putri Minas (E-Jurnal Medika Udayana; Vol 10 No 12 (2021): Vol 10 No 12(2021): E-Jurnal Medika Udayana, 2021)
Background: Diabetes Mellitus (DM) is one of the diseases with an increasing incidence rate. One of the influential factors in DM is life style. The purpose of this study is to find out the relationship between age, diet, and stress with the incidence of DM. Method: This study is a cross-sectional study that has been conducted ethical clearance of previous research. Sampling techniques were conducted using accidental sampling with 89 of samples. Data is collected by using guided interviews and FFQ (Food Frequency Questionnaire). Results: Bivariate analysis by using chi-square found that there is a relationship of DM to obesity (p-value = 0.021), DM to diet (p-value = 0.000), and DM to stress levels (p-value = 0.008). So that by maintaining diet, stress management, and weight control can decrease the risk of DM.